Axonal neuropathy in female carriers of the fragile X premutation with fragile x–associated tremor ataxia syndrome. Issue 2 (August 2015) - Ram, Suresh; Devapriya, Inoka A.; Fenton, Grace; Mcvay, Lindsey; Nguyen, Danh V.; Tassone, Flora; Maselli, Ricardo A.; Hagerman, Randi J.
ABSTRACT Introduction: In this study we examined whether females with the fragile X–associated tremor ataxia syndrome (FXTAS) and non‐FXTAS premutation carriers have electrophysiological signs of underlying peripheral neuropathy. Methods: Nerve conduction studies (NCS) were performed on 19 women with FXTAS, 20 non‐FXTAS carriers, and 26 age‐matched controls. The results were compared with existing data on corresponding male carriers. Results: Women with FXTAS and non‐FXTAS carriers had reduced sensory nerve action potential amplitudes. Also, there was a strong trend for reduced compound muscle action potential amplitudes in women with FXTAS, but not in non‐FXTAS carriers. No significant slowing of nerve conduction velocities, prolongation of F‐wave latencies, or associations with molecular measures was observed. Conclusions: This study suggests an underlying axonal neuropathy in women with FXTAS. However, in comparison to men with FXTAS, the NCS abnormalities in women were less severe, possibly due to the effect of a normal X chromosome. Muscle Nerve52: 234–239, 2015